2021
DOI: 10.1111/bjso.12496
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling national and religious identification as predictors of support for religious minority rights among Christian majority groups

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 80 publications
0
5
0
1
Order By: Relevance
“… This study complements a previously published study based on the same data set, by taking a motivational approach. Our previous study (Eskelinen et al, 2022) showed that while national identification was not associated with support for Muslims’ or other religious minorities’ rights, higher religious identification predicted higher support for these rights. Both forms of identification were associated with higher perceived diversity threat.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“… This study complements a previously published study based on the same data set, by taking a motivational approach. Our previous study (Eskelinen et al, 2022) showed that while national identification was not associated with support for Muslims’ or other religious minorities’ rights, higher religious identification predicted higher support for these rights. Both forms of identification were associated with higher perceived diversity threat.…”
mentioning
confidence: 87%
“…The direction of estimates mostly remained the same, but the interactions were not significant, likely attributable to a significant drop in sample sizes. Finally, we checked that changing the dependent variable into support for the rights of Muslims living in [Australia/Finland/Germany/Norway] (reported in Eskelinen et al, 2022) did not change the pattern of findings. The results of these additional analyses can be found in the Supporting Information.…”
Section: Structural Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been found that individuals respond to various existential threats by derogating outgroups (Stephan, 2014), favouring ingroups (Giannakakis & Fritsche, 2011), or excluding minorities (Van der Zee & Van der Gang, 2007). Previous research has specifically shown that perceived symbolic (cultural) (Eskelinen et al, 2022) and realistic (material) threats (Esses, Dovidio, Jackson, & Armstrong, 2001) are both associated with more negative attitudes towards Muslims. Nevertheless, it seems that at best, perceived threats can also bring people together.…”
Section: Existential Threats and Attitudesmentioning
confidence: 99%
“…Так как Европа тоже столкнулась с ростом террористической деятельности и иммиграционным потоком, там, как и в российской психологии, обсуждаются проблемы терроризма (Fischer-Preßler et al, 2019). Большая группа исследований посвящена поиску взаимопонимания между представителями различных религий (Eskelinen et al, 2022;Husain, 2020;Edwards, 2018;Mansouri & Vergani, 2018) и интеграции беженцев (Albanesi et al, 2019), куда включаются общественный контекст (Akbarzadeh & Roose, 2011), различия культурных ценностей, проблема национальной идентичности (van der Werf et al, 2022).…”
unclassified